MARKET OVERREACTION, SIZE EFFECT ATAU LIQUIDITY EFFECT? STUDI PADA BURSA EFEK INDONESIA - Octavio, Danes Quirira; Lantara, I Wayan Nuka (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 1 Tahun 2014)
This paper examines whether the anomalies of market overreaction and size effect and or liquidity effect occur on the Indonesia Stock Exchange.We also test the anomalies over short period and longer-term period. The  sample of this research comprises of stocks listed in the KOMPAS 100 index from January 2010 – July 2010. The stocks listed in KOMPAS 100 index are considered as active stocks and provide great influence on the movement Indonesian Capital Market Composite Index (IHSG). Stocks are grouped into two portfolio samples: winner portfolio and loser portfolio. Results depict that only market overreaction occurred and only in loser portfolio.We also find that the market overeaction occur only in short period (6 months). We further test the size effect and liquidity effect. The finding shows that size matter in explaining market overeaction on loser portfolio
Keywords: abnormal return, market overreaction, size effect, liquidity effect